THE EFFECT OF ADDITION OF JAMBAL SIAM FISH (Pangasius hypophthalmus) MEAT IN BANANA HEART(Musa paradisiaca) NUGGET ON CONSUMER ACCEPTANCE - Wahyu Oloan Sagala; N. Ira Sari; Mery Sukmiwati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The aims of this research to determine the effect of addition of Jambal Siam fish meat (Pangasius hypophthalmus) in banana heart (Musa paradisiaca) nugget on consumer acceptance. This research used an experimental method with a completely randomized design (CRD) non factorial. The addition in the making banana heart nugget was using Jambal siam fish meat in different amounts. The results showed that banana heart nugget with the addition of jambal siam fish meat very real influence on the value of the organoleptic appearance, flavors, aroma, texture, water content, protein, fat and crude fiber. Based on the level of consumer acceptance and parameters tested, nugget with the addition of 350 grams of Jambal siam fish meat shows the best mix because it is so favored by consumers, namely 75 (93.75%) with such criteria (gray, golden yellow and bright), flavors (banana heart does not feel and taste of the fish meat more dominant), aroma (smell of fish is more dominant so it does not smell of banana) texture (soft, dense and fit) with water content of 37.55%, 30.43% protein, 8.64% fat and 4.81% crude fiber content. The parameters tested in the study was the organoleptic value , chemical analysis and coarse fibers.Keywords : Jambal siam fish meat, banana hearts nugget, consumer acceptance